Lifetime violence and suicidal ideation among young women (18–24 years) in Uganda: Results from a population-based survey - Kisaakye, Peter; Kafuko, Agatha; Bukuluki, Paul (Frontiers in Global Women's Health, 2023)
Violence is a major global public health issue that threatens the physical and mental health of victims. Of particular concern is the increasing evidence which suggests that violence is strongly associated with suicidal behavior including ideation. This study therefore seeks to understand the relationship between lifetime violence and suicide ideation using a nationally representative sample of 1,795 young women (18-24 years) in Uganda. Results indicate that respondents who experienced lifetime sexual violence (aOR=1.726; 95%CI=1.304-2.287), physical violence (aOR=1.930; 95%CI=1.293-2.882) or emotional violence (aOR=2.623; 95%CI=1.988-3.459) were more likely to experience suicide ideation. Respondents who were not married (aOR=1.607; 95%CI=1.040-2.484), not having too much trust with community members (aOR=1.542; 95%CI=1.024-2.320) or not having a close relationship with biological parents (aOR=1.614; 95%CI=1.230-2.119) were more likely to experience suicide ideation. Respondents who did not engage in work in the past 12 months prior to the survey (aOR=0.629; 95%CI=0.433-0.913) were less likely to experience suicide ideation. The results can be used to inform policy and programming and for integration of mental health and psychosocial support in programming for prevention and response to violence against young women.